Women Neuroscientist Disciples of Pío del Río-Hortega: the Cajal School Spreads in Europe and South America - Nombela, Cristina; Fernández-Egea, Emilio; Giné, Elena; Worbe, Yulia; del Río-Hortega Bereciartu, Juan; de Castro, Fernando (Frontiers in Neuroanatomy, 2021)
Pio del Rio-Hortega was not only the discoverer of the microglia and oligodendroglia but also possibly the most prolific mentor of all Santiago Ramon y Cajal´s disciples (Nobel awardee in Physiology or Medicine 1906 and considered as the father of modern Neuroscience). Among Río-Hortega´s mentees, three exceptional women are frequently forgotten, chronologically: Pio’s niece Asunción Amo del Río who worked with Río-Hortega at Madrid, Paris, and Oxford; the distinguished British neuropathologist Dorothy Russell who also worked with Don Pío at Oxford, and Amanda Pellegrino de Iraldi, the last mentee in his career. Here we introduce and discuss the research and contributions of these women at Río-Hortega´s laboratory and thereafter for better comprehension of the History and its frame. The present work completes the contribution of women neuroscientists that worked with Cajal and his main disciples of the Spanish Neurological School both in Spain (previous work) and in other countries (present work).